1976
DOI: 10.1111/j.1399-3054.1976.tb03985.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Deoxyribonucleic Acid Metabolism and Membrane Fatty Acid Content Related to Chilling Resistance in Germinating Cotton (Gossypium barbadense)

Abstract: Chilling damage was examined in the chilling‐sensitive plant Gossypium barbadense. Between 30 and 36 h of germination at 34°C, the seedlings are extremely sensitive to temperatures below 10°C. The initiation of chilling damage by exposure to 2°C for 5 h during the sensitive period resulted in a large reduction in DNA synthesis. The reduction was correlated with a reduced efficiency of nuclear DNA polymerase activity. Comparing a more chilling resistant genotype to a more sensitive variety indicated that the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Although such enhancement of the leakage has not been fully proven at around the lower limit temperatures, Bramlage, Leopold & Parrish (1978) who investigated the chilling stress on soybean embryos during imbibition concluded that chilling injury resulted from abnormal organization of the cell membranes at low temperatures below the phase change ternperature of the membrane phospholipids. The emergence of cotton seeds from cold soil has also been positively correlated with the unsaturated/satur-ated fatty acid ratio of membrane lipids (Clay, Bartkowski & Katterman, 1976). The leakage phenomenon may not necessarily be the cause of germination failure at lower temperatures, but may be a par'allel phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Although such enhancement of the leakage has not been fully proven at around the lower limit temperatures, Bramlage, Leopold & Parrish (1978) who investigated the chilling stress on soybean embryos during imbibition concluded that chilling injury resulted from abnormal organization of the cell membranes at low temperatures below the phase change ternperature of the membrane phospholipids. The emergence of cotton seeds from cold soil has also been positively correlated with the unsaturated/satur-ated fatty acid ratio of membrane lipids (Clay, Bartkowski & Katterman, 1976). The leakage phenomenon may not necessarily be the cause of germination failure at lower temperatures, but may be a par'allel phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Amruthesh et al (2005) investigated the role of unsaturated fatty acids in the resistance of pearl millet to downy mildew, and found that its stimulation induced strong plant resistance [2]. Clay et al (2006) found that the host resistance was related to the higher content of unsaturated fatty acids in the nuclear membrane of resistant species on Gossypium barbadense [16].…”
Section: Discussionmentioning
confidence: 99%
“…For germinating seeds, low temperature interferes with the ability of the embryo to be transformed from a quiescent body into a metabolically active organ [10], resulting in failure of germination and poor growth vigour. Chilling-resistant cultivars can stand the low temperature imbibition and germinate well, whereas the seed germination process is severely affected in chilling sensitive phenotypes [18][19][20][21][22]. Cheng et al [23] observed that the soybean seeds imbibed at 22°C germinated within 24 h, whereas seeds imbibed at 4°C did not germinate within 24 h. When transferred to 22°C, germination was observed in about 20% of the seeds.…”
Section: Low Temperature Effects Seed Germinationmentioning
confidence: 99%